Hubungan Media Sosial dengan Kesadaran Beragama Siswa MTs Persatuan Umat Islam Bondongan Kota Bogor - Rosada, Helmi Yahya; Makarim, Chodidjah (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Social media has become a common tool for all groups, both adults and students, the influence of social media is so great that it can influence human awareness in living life, especially in religion. All forms of problems spread on social media regarding human behavior in religion, can be seen from various kinds of news that is social media a very influential factor for religious awareness? Therefore, researchers sought to find out the relationship between social media and religious awareness using quantitative research methods. This research distributed questionnaires to students with a sample size of 52 students from a population of 125 which aims to find out whether there is a relationship between social media and religious awareness among MTS students of the Islamic Community Association of Bogor City with the results that there is a significant relationship between social media and it can be seen that social media is the biggest factor in reducing religious awareness. The level of religious awareness at the Islamic Community Association MTS is considered to be in the high category using Likert Scale calculations. So the researchers concluded that there is a relationship between social media and religious awareness.